2002
DOI: 10.1002/humu.9053
|View full text |Cite
|
Sign up to set email alerts
|

A founder mutation (R254X) of SLC22A5 (OCTN2) in Chinese primary carnitine deficiency patients

Abstract: Mutations in the SLC22A5 gene, which encodes for the plasma membrane carnitine transporter OCTN2, cause primary carnitine deficiency (PCD). After our first report of OCTN2 mutations in Chinese, three more Chinese PCD patients were identified. The parents of these families were non-consanguineous and these families were unrelated. Two novel truncating mutations were found: R254X, a single-base mutation at cDNA position 981 (c.981C>T); and Y387X (c.1382T>G). Two probands, one each from Taiwan and Macau, were hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
4
30
0
1
Order By: Relevance
“…Two newborns did not receive the mutation analysis and were lost for follow-up. A prevalent founder mutation, c.981C>T (p.R254X) of the SLC22A5 gene has been identified in Taiwan and in other southern Chinese populations (Tang et al 2002). The estimated incidence of CTD is from 1/62,500 to 1/15,625 (Tang et al 2002;Lee et al 2009), which is higher than the incidence found in our study (1/ 118,543).…”
Section: Carnitine Transporter Defectmentioning
confidence: 46%
“…Two newborns did not receive the mutation analysis and were lost for follow-up. A prevalent founder mutation, c.981C>T (p.R254X) of the SLC22A5 gene has been identified in Taiwan and in other southern Chinese populations (Tang et al 2002). The estimated incidence of CTD is from 1/62,500 to 1/15,625 (Tang et al 2002;Lee et al 2009), which is higher than the incidence found in our study (1/ 118,543).…”
Section: Carnitine Transporter Defectmentioning
confidence: 46%
“…Most of the mothers affected by CUD were asymptomatic . The carrier rate of the more severe CUD mutation in the Southern Chinese population, p.R254X, is approximately 1 in 125 (Tang et al 2002). This mutation represented 50% of all mutations in clinically detected cases of CUD but represented only 30% of all mutations in NBS-detected cases (Lee et al 2010), suggesting a decrease in the severity of the disease in the latter group of patients.…”
Section: Discussionmentioning
confidence: 94%
“…The lack of several transmembrane domains may cause degraded or nonfunctional protein product. R254X, previously described mutation, was reported in Chinese and Saudi Arabians, whereas R282X was a common mutation in Caucasians (Burwinkel et al 1999;Lamhonwah et al 2004;Tang et al 2002;Vaz et al 1999;Wang et al 1999). Other 1-bp deletion c.1009delA (T337Pfs12X) results in a frameshift with Thr337Pro leading to a predicted truncated protein of 347 aa length (Lamhonwah et al 2002).…”
Section: Discussionmentioning
confidence: 97%